2006
DOI: 10.1002/bem.20216
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of rat brain to 915 MHz GSM microwaves induces changes in gene expression but not double stranded DNA breaks or effects on chromatin conformation

Abstract: We investigated whether exposure of rat brain to microwaves (MWs) of global system for mobile communication (GSM) induces DNA breaks, changes in chromatin conformation and in gene expression. An exposure installation was used based on a test mobile phone employing a GSM signal at 915 MHz, all standard modulations included, output power level in pulses 2 W, specific absorption rate (SAR) 0.4 mW/g. Rats were exposed or sham exposed to MWs during 2 h. After exposure, cell suspensions were prepared from brain samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
1
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 57 publications
2
66
1
3
Order By: Relevance
“…The animals are exposed to RF EMFs in the same TEM-cells (Figure 1 Belyaev et al [5]. These TEM-cells have been designed by dimensional scaling from previously constructed cells at the National Bureau of Standards [6], which are known to generate uniform TEM-fields for standard measurements.…”
Section: Gsm Exposurementioning
confidence: 99%
“…The animals are exposed to RF EMFs in the same TEM-cells (Figure 1 Belyaev et al [5]. These TEM-cells have been designed by dimensional scaling from previously constructed cells at the National Bureau of Standards [6], which are known to generate uniform TEM-fields for standard measurements.…”
Section: Gsm Exposurementioning
confidence: 99%
“…The exposure of human lens epithelial cells (HLEC) to microwaves of 1800 MHz resulted in repairable DNA damage [9,18]. However, some studies have shown absence of DNA damage in human lymphocyte and leukocyte culture on exposure to RFR emitted from cell phone [19][20][21] and in rat brain exposed to 915 MHz GSM microwaves [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that ionizing radiation, such as X-ray, affects biological systems, while it is still unclear and inconclusive whether non ionizing low-energy RF radiation could have effects on them. Although there have been a lot of studies of RF effects on biological systems for various aspects, most of them have focused on stress proteins, such as HSP, and MAPK signaling or DNA damages (Belyaev et al, 2006;Chauhan et al, 2006;Friedman et al, 2007;Lee et al, 2006;Sanchez et al, 2007;Sanchez et al, 2008, Verschaeve et al, 2009. For instance, Friedman et al (2007) found that exposure of HeLa and Rat1 cells to 875 MHz RF radiation induces the activation of the ERK cascade through ROS generation via NADH oxidase but not that of JNKs or p38 MAPKs.…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies on the biological effects of RF exposure could not detect any molecular changes, some reports demonstrated RF-specific gene expression (Belyaev et al, 2006;Lee et al, 2005;Nylund et al, 2006). For example, Lee et al (2005) used the serial analysis of gene expression (SAGE) technique and found that 2.45 GHz RF radiation at a 10-W/kg SAR for 2∼6 h affected the expression of 221 genes, including apoptosis-related genes and cell cycle genes, in human HL-60 cells without a significant increase of HSP expression.…”
Section: Introductionmentioning
confidence: 99%